2013
DOI: 10.1139/cjz-2013-0181
|View full text |Cite
|
Sign up to set email alerts
|

Population fluctuations and distribution of staging Eared Grebes (Podiceps nigricollis) in North America

Abstract: Eared Grebes (Podiceps nigricollis Brehm, 1831) use saline ecosystems throughout much of their life cycle, and greater than 90% of the North American population stage during fall at two hypersaline lakes. At one of these lakes, Great Salt Lake (GSL), Utah, a commercial harvest of brine shrimp (Artemia franciscana Kellogg, 1906) cysts occurs during fall and may impact Eared Grebe populations. We used photo surveys on the other hypersaline lake, Mono Lake, California, and on the GSL, as well as aerial counts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The likely origin of the nonlocal grebes corresponded to much of the breeding area from approximately the latitude of the Great Salt Lake and northward, whereas the likely region of origin of the local individuals included nonbreeding areas to the south of the Great Salt Lake, which includes Mono Lake and the sites where the carcasses were found (Figure 6c). Our results showed that a higher proportion of eared grebes had likely molted at the Great Salt Lake than at Mono Lake, which is consistent with historic population patterns at the two lakes (Roberts et al., 2013). This correspondence indicates there may be instances in which stable isotope data can be used to better understand species‐level distributions for species less well known than these grebes.…”
Section: Discussionsupporting
confidence: 90%
“…The likely origin of the nonlocal grebes corresponded to much of the breeding area from approximately the latitude of the Great Salt Lake and northward, whereas the likely region of origin of the local individuals included nonbreeding areas to the south of the Great Salt Lake, which includes Mono Lake and the sites where the carcasses were found (Figure 6c). Our results showed that a higher proportion of eared grebes had likely molted at the Great Salt Lake than at Mono Lake, which is consistent with historic population patterns at the two lakes (Roberts et al., 2013). This correspondence indicates there may be instances in which stable isotope data can be used to better understand species‐level distributions for species less well known than these grebes.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to cyst removal by waterfowl, eared grebes occupying the GSL from October through December consumed 11% of combined harvest and eared grebe consumption (Roberts and Conover ), an order of magnitude more than ducks. Though eared grebe diets contain fewer brine shrimp cysts than shovelers or teal (Roberts and Conover ), their populations on the GSL are substantially greater, with yearly populations regularly reaching greater than 1.5 million birds (Roberts et al ). No other avian species occurs on pelagic areas of the GSL during winter months so the combined duck and eared grebe cyst removal likely accounts for all avian cyst depletion sources.…”
Section: Discussionmentioning
confidence: 99%
“…Although all bird detections tend to increase at the beginning of the fall period in September, detections of water associates and water obligates continued to increase until the end of October, whereas detections of other birds declined steadily throughout the fall. Waterfowl, loons, and grebes are all known to move in comparatively large numbers in fall when weather conditions are favorable for migration [31,32,33]. Eared grebes stage at the Great Salt Lake in Utah, and synchronize migration with upwards of 100,000 to 200,000 birds departing simultaneously en route to the Gulf of California [34].…”
Section: Phenologymentioning
confidence: 99%